Zambia - Public Expenditure Review : Resource Allocations and Financial Flows in the Water Sector in Zambia - World Bank (Washington, DC, 2013)
Zambia initiated a series of reforms in the early 1990s aimed at increasing sustainable water supply and sanitation services. This was coupled with improving water resources management and enhancing contributions to economic growth and development. The reforms are embedded within seven sector principles that were articulated in the 1994 National Water Policy (NWP). The aim of the NWP was 'to promote sustainable water resources development with a view to facilitate an equitable provision of adequate quantity and quality of water for all competing groups of users at acceptable costs and ensuring security of supply under varying conditions.' The objective of this paper is to review the resource allocations and financial flows in the water sector. It is the first in a series of five policy papers that includes the following: resource allocations and financial flows in water sector; comparative analysis of opportunity costs of water supply in low cost and Peri-Urban areas; equity and efficiency of rural water supply support in Zambia; economic analysis of the impact of small dams on rural poverty in Zambia; and priority policy measures to improve public expenditures in water sector.